Protocol for a multicentre, multistage, prospective study in China using system-based approaches for consistent improvement in surgical safety. Issue 6 (15th June 2017) - Yu, Xiaochu; Jiang, Jingmei; Liu, Changwei; Shen, Keng; Wang, Zixing; Han, Wei; Liu, Xingrong; Lin, Guole; Zhang, Ye; Zhang, Ying; Ma, Yufen; Bo, Haixin; et al.
Abstract : Introduction: Surgical safety has emerged as a crucial global health issue in the past two decades. Although several safety-enhancing tools are available, the pace of large-scale improvement remains slow, especially in developing countries such as China. The present project (Modern Surgery and Anesthesia Safety Management System Construction and Promotion) aims to develop and validate system-based integrated approaches for reducing perioperative deaths and complications using a multicentre, multistage design. Methods and analysis: The project involves collection of clinical and outcome information for 1 20 000 surgical inpatients at four regionally representative academic/teaching general hospitals in China during three sequential stages: preparation and development, effectiveness validation and improvement of implementation for promotion. These big data will provide the evidence base for the formulation, validation and improvement processes of a system-based stratified safety intervention package covering the entire surgical pathway. Attention will be directed to managing inherent patient risks and regulating medical safety behaviour. Information technology will facilitate data collection and intervention implementation, provide supervision mechanisms and guarantee transfer of key patient safety messages between departments and personnel. Changes in rates of deaths, surgical complications during hospitalisation, length of stay, system adoption and implementation rates will be analysed to evaluate effectiveness and efficiency. Ethics and dissemination: This study was approved by the institutional review boards of Peking Union Medical College Hospital, First Hospital of China Medical University, Qinghai Provincial People's Hospital, Xiangya Hospital Central South University and the Institute of Basic Medical Sciences, Chinese Academy of Medical Sciences. Study findings will be disseminated via peer-reviewed journals, conference presentations and patent papers.